2016
DOI: 10.1016/j.watres.2016.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced formation of bromate and brominated disinfection byproducts during chlorination of bromide-containing waters under catalysis of copper corrosion products

Abstract: a b s t r a c tCopper corrosion products (CCPs) in water distribution pipes may catalyze the reactions among disinfectant, natural organic matter (NOM), and bromide (Br À to a lesser extent because of the water matrix effect. In mechanism, the CCPs promoted the formation of BrO 3 À and Br-DBPs through catalyzing the HOBr disproportionation pathway and the reaction of HOBr toward HA, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…7). Bromine species (HOBr/OBr-) were known to be more effective substitution agents than the corresponding chlorine species, so increasing bromide concentrations shifted the distribution of di-HANs, including DCAN, BCAN, and DBAN, from DCAN to BCAN and then to DBAN (Bond et al, 2011;Hu et al, 2016).…”
Section: Effect Of Bromidementioning
confidence: 99%
“…7). Bromine species (HOBr/OBr-) were known to be more effective substitution agents than the corresponding chlorine species, so increasing bromide concentrations shifted the distribution of di-HANs, including DCAN, BCAN, and DBAN, from DCAN to BCAN and then to DBAN (Bond et al, 2011;Hu et al, 2016).…”
Section: Effect Of Bromidementioning
confidence: 99%
“…Results indicated that the reactivity of HOBr with phenols was much stronger than that of the HOBr disproportionation in the presence of CuO, whereas the disproportionation of HOBr prevails in comparison with the reactions of HOBr with certain less reactive compounds, such as acetone, butanol, propionic and butyric acids (Liu and Croué, 2016). Hu et al (2016) reported that three CCPs (i.e. Cu(II), Cu2O and CuO) simultaneously enhanced the formation of bromate and Br-DBPs during chlorination of bromide-containing waters.…”
Section: 【Figure 3】mentioning
confidence: 99%
“…It was reported that the concentrations of bromate and Br-DBPs (i.e. THMs, HAAs and HAMs) under CuO, Cu2O or Cu(II) catalysis were generally lower than the maximum contaminant level at the Brconcentration of 0.2 mg/L (Hu et al, 2016). However, when the Brconcentration increased to 0.5 mg/L, the concentration of bromate after the CuO, Cu2O or Cu(II) catalysis significantly increased, ranging from 15.1 -54.6 μg/L, and the enhancement ratios of Br-DBPs (i.e.…”
Section: 【Figure 3】mentioning
confidence: 99%
“…Cu­(II), Cu 2 O, and Cu­(OH) 2 are three kinds of copper corrosion products, which form in copper pipes when disinfectant residues travel through them. Moreover, CuO and Cu 2 (OH) 2 CO 3 are two main kinds of copper corrosion products. , The current studies on copper corrosion products mainly focus on the catalytic behaviors during the disinfection process. ,, There has been no systematic study on the catalytic reduction of pollutants with Fe(0) using the solid copper corrosion products. The enhancement of Cu­(OH) 2 on the reduction of NDMA with Fe(0) portended the catalytic abilities of solid copper corrosion products.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 The current studies on copper corrosion products mainly focus on the catalytic behaviors during the disinfection process. 20,22,23 There has been no systematic study on the catalytic reduction of pollutants with Fe(0) using the solid copper corrosion products. The enhancement of Cu(OH) 2 on the reduction of NDMA with Fe(0) 19 portended the catalytic abilities of solid copper corrosion products.…”
Section: Introductionmentioning
confidence: 99%